COGNITIVE LOAD REDUCTION IN ARABIC NUMERACY: A MA'DUD CLASSIFICATION APPROACH - Yaqin, Muhammad Ainul; Huda, Hisbullah; Khair, Nafilatul; Wafa, Muhammad Ali; Amin, Sohibul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The learning of Arabic numeracy (ʿadad wa al-maʿdūd) in many Islamic boarding schools is still dominated by a grammatical approach based on five complex number categories, often resulting in high cognitive load, frequent errors, and low student confidence. This study aims to examine the effectiveness of the Maʿdūd Classification method, which simplifies traditional classification into two main paths—mudhakkar and muʾannath—implemented through seven systematic teaching stages to reduce cognitive burden and improve Arabic numeracy mastery. The study employed a mixed-method design using a quasi-experimental one-group pretest–posttest model involving 30 beginner-level students at Darul Lughah Waddirasatil Islamiyah Islamic Boarding School, supported by interviews and participatory observation. The Paired Samples t-test showed a significant increase in mean scores from 46.00 to 88.07 (t = −81.49, df = 29, p 0.001), along with reduced standard deviation and coefficient of variation, indicating more consistent learning outcomes. Qualitative findings confirmed reduced memorization demands, clearer conceptual patterns, and a more positive learning experience. These results demonstrate that Maʿdūd Classification is an effective cognitive-load-based instructional model for improving Arabic numeracy literacy.